2016
DOI: 10.1007/s10461-016-1398-6
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use and Adherence Among People Living with HIV/AIDS Receiving cART in Latin America

Abstract: This cross-sectional study describes substance use prevalence and its association with cART adherence among 3343 individuals receiving care at HIV clinics in Argentina, Brazil, Chile, Honduras, Mexico, and Peru. A rapid screening tool evaluated self-reported 7-day recall of alcohol, marijuana, cocaine, heroin, and methamphetamine use, and missed cART doses. Overall, 29.3% individuals reported having ≥ 1 alcoholic drinks, 5.0% reported any illicit drug use and 17.0% reported missed cART doses. In the logistic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 40 publications
(45 reference statements)
3
28
1
Order By: Relevance
“…The prevalence of 90-day alcohol use (30.1%), marijuana use (3.9%), and crack/cocaine use (3.1%) was similar to a one-week prevalence found in the same cohort, 34 although 90-day tobacco use (19.5%) was smaller than that of 12-month use (29%), 33 as expected. All estimates, however, were lower than that of U.S. HIV-infected cohorts, where 50–70% report smoking, 35 53% report drinking in the past month, 36 and 24 and 9% report 90-day marijuana and crack/cocaine use, respectively.…”
Section: Discussionsupporting
confidence: 80%
“…The prevalence of 90-day alcohol use (30.1%), marijuana use (3.9%), and crack/cocaine use (3.1%) was similar to a one-week prevalence found in the same cohort, 34 although 90-day tobacco use (19.5%) was smaller than that of 12-month use (29%), 33 as expected. All estimates, however, were lower than that of U.S. HIV-infected cohorts, where 50–70% report smoking, 35 53% report drinking in the past month, 36 and 24 and 9% report 90-day marijuana and crack/cocaine use, respectively.…”
Section: Discussionsupporting
confidence: 80%
“…The flow diagram of study selection is shown in Figure . Fifty‐three studies, composed of 22,603 participants in ART from 25 LAC countries, met eligibility criteria for the systematic review (Table ) . The median number of participants in ART per study was 201 [range: 13 – 3343; interquartile range (IQR): 394 – 125].…”
Section: Resultsmentioning
confidence: 99%
“…In an analysis of the same cohort, periods of active injection drug use were associated with transitions out of optimal adherence and as barriers to becoming optimally adherent [20]. Another study conducted among 3,343 PLHIV in care across six countries from Latin America in 2012–2013 found that between 29% and 46% of people who used alcohol or illicit drugs reported missing ART doses in the prior week, compared to only 11% of individuals who did not report substance use [17]. …”
Section: Recent Trends In Art Adherence Among Pwudmentioning
confidence: 99%
“…A recent review examining the impacts of alcohol on the HIV cascade of care continuum published between 2010 and 2015 found an association between alcohol use and nonadherence, usually in a dose-response fashion, in most (n=16) of the 33 included studies focusing on the ART adherence step [22]. Other recent studies confirm this negative influence of alcohol on ART adherence in a variety of contexts [23, 17, 24, 25]. …”
Section: Specific Substances and Art Adherencementioning
confidence: 99%